UJI EFEKTIVITAS REBUSAN DAUN KEJIBELING (Strobilanthes crispus) SEBAGAI ANTIDIABETES TERHADAP TIKUS GALUR WISTAR YANG DIINDUKSI ALOKSAN - Susi Wijaya; Sugiono Sugiono (Sekolah Tinggi Ilmu Kesehatan Tujuh Belas, Karanganyar, JAwa, Indonesia, 2022)
Kejibeling is a plant that is very easy to find in the Pulosari area, but its use is still very rare. In general, the people of the Pulosari area understand more or less what benefits are contained in the kejibeling plant, especially the kejibeling leaves, where the leaves can be useful as anticancer, antidiabetic, immunity enhancer, and anticholesterol. Diabetes is now affecting many women and teenagers because of the poor lifestyle of millennials due to the abundance of fast food. Plus the use of traditional plants is starting to be abandoned. The research used Wistar mice because this type of mouse is often found and their metabolism is very fast, with these advantages these mice are suitable as test animals. This study aims to determine the indications of kejibeling leaf boiled water and determine the effective dose of kejibeling leaf boiled water on Wistar rats that have been induced by alloxan. The research methods include making a decoction of kejibeling leaves, which was tested in vivo on Wistar rats induced by alloxan and identifying secondary metabolites in decoction of Kejibeling leaves (Strobilanthes crispus). Where the research results were seen from the percentage at 30 minutes after treatment, for the group of mice given the negative control distilled water, the percentage reduction in blood sugar levels was 11.74%, for the group of mice given the 2000mg dose of kejibeling leaf decoction was 13.81%, for the group of mice given boiled kejibeling leaves at a dose of 3540mg was 16.16%, the group of rats given boiled kejibeling leaves at a dose of 6300mg was 31.29% and the group of rats given metformin as a positive control was 36.91%.